Human Menopausal Gonadotropins in Combination for Stimulation does not Improve IVF Outcomes in POSEIDON Group 4 Patients, When Compared to Recombinant Follicle Stimulating Hormone Alone: A Prospective Randomized, Non-Blinded, Controlled Pilot Trial - Jiahui Qiu; Shan Luo; Yu Bai; Xun Zeng; Xiaohong Li (IMR Press, 2023)
Background: To evaluate whether the addition of human menopausal gonadotropin (HMG) during the early follicular phase of controlled ovarian stimulation improves clinical outcomes in patients classified as group 4 on the Patient-Oriented Strategy Encompassing IndividualizeD Oocyte Number (POSEIDON) classification. Methods: A prospective, randomized, and non-blind controlled trial was conducted, involving 172 patients seeking infertility treatment with an indication for in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Among them, 78 patients were randomly assigned to the HMG/follicle stimulating hormone (FSH) group, receiving 75 IU of HMG for FSH on either day 2 or day 3 of menstruation, while 94 patients were assigned to the FSH monotherapy group. Results: The total dose of gonadotropin used in the HMG/FSH group (2510.77 ± 368.11) was higher than that in the FSH alone group (2310.98 ± 641.33), indicating greater medication usage (p < 0.001). In terms of the mean number of retrieved oocytes and good quality embryos, the HMG supplementation group demonstrated a slight increasing trend (3.79 and 1.43, respectively) compared to the FSH alone group (3.44 and 1.16, respectively), though these differences did not show statistical significance. There is no significant difference in the outcomes of ongoing pregnancy rates, biochemical pregnancy rates, or clinical pregnancy rates per end-cycle or embryo transfer cycle between the two groups. Conclusion: The addition of HMG to FSH during the early follicular phase for IVF/ICSI did not provide any benefits for patients classified as group 4 on the POSEIDON classification. Clinical Trial Registration: The study was registered at Chinese Clinical Trial Registry (https://www.chictr.org.cn), registration number: ChiCTR2100043040.